A STRUGGLE FOR LIFE OF CHUCK NOLLAND ROBERT ZEMECKIS'S CAST AWAY: AN INDIVIDUAL PSYCHOLOLOGICAL APPROACH - PUTRI , ANIS DYAH ERFIANTI DWI (2007)
The problem of this study is to reveal how the struggle for life on the major characther. The objectives of this study are to ana lyze the movie based on the structural elements and to analyze the struggle of life on the major character on Robert Zemeckis's Cast Away based on Individual Psychological analysis. This study is a literary study, which can be categorized into a qualitative study. The object of this study is Robert Zemeckis Cast Away movie. The data sources are primary and secondary data sources. The primary data sources are the movie Cast Away script, and the secondary data are related to the primary data that support the analysis such as some books and of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that, the problem faced by the major character is his struggle to go out of his condition, it causes his to use individual psychological perspective such as: Inferiority Feeling and Compensation, Striving for Supe riority, Fictional Finalism, Style of Life, Social Interest, Creative Power by using this method Chuck Noland as the major character can solve his problem.